Kajian Heuristik dan Hermeneutik Lirik Lagu “Gala Bunga Matahari” Karya Sal Priadi - Rano Hidayat; Jaeni Jaeni; Yahfenel Evi Fussalam (Universitas Sultan Ageng Tirtayasa, 2026)
In the world of Indonesian music, Sal Priadi is one of the Indonesian musicians who stands out for his unique ability to create song lyrics that not only serve as melodic accompaniment, but also as works of literary art rich in meaning and aesthetics. As a singer and songwriter, he is known for his ability to transform everyday language into poetic and profound expressions, creating a listening experience that not only touches the heart but also provokes thought. The lyrics in a song are crucial for literary aesthetics, not only regarding the depth of the lyrics, but also the connection of the meaning of the lyrics themselves to the audience, so that the meaning of a song reaches the audience. Of course, the task of songwriters is to understand the conditions of their society. Analyzing a work of art certainly requires a methodical approach to provide perspective on the work so as to be able to provide an objective explanation. In this methodological approach, the author uses the semiotic approach of Michael Rifatere using heuristic and hermeneutic studies.